Application od Base Isolation as a Seismic Retrofitting Techniques - Alahdab, Waled (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Seismic performance of reinforced concrete structures is indeed one of the most critical points when it comes to human life safety. For many years, scientists were trying to find a way to accurately assess the structural behavior of buildings under severe earthquake records, and to implement a way to improves the performance of the structure. This study is aiming to evaluate the seismic performance of reinforced concrete structures using two main methods which are the equivalent lateral load method and the time history analysis to assess the performance of the building and define the deficiency points. Thereafter a retrofitting strategy is planned to be handled through the applications of different types of base isolations ( lead core rubber bearing, flat sliding bearing, and friction pendulum bearing) on an existed low-rise building to check the capability of the isolators to improve the building performance against earthquake records, and to check how isolators are capable of decreasing the story accelerations in the higher stories, which helps in reducing the damage of the nonstructural elements. Results indicate that lead core rubber bearing isolator show the maximum reduction for the accelerations in the higher stories which reflect its outstanding performance with the respect the other considered types.

ÖZ: Betonarme yapıların sismik performansı, insanların yaşam güvenliği açısından gerçekten en önemli noktalardan biridir. Uzun yıllar boyunca, bilim adamları, şiddetli deprem kayıtları altındaki binaların yapısal davranışlarını doğru bir şekilde değerlendirmek ve yapının performansını iyileştirmek için metotlar bulmak ve uygulamak için çalışmaktadırlar. Bu çalışma, betonarme yapıların sismik performansını, eşdeğer yanal yük yöntemi ve binanın performansını ve eksik noktalarını tanımlamak için zaman tanım alanında analizini kullanarak değerlendirmeyi kapsayan iki ana yöntemi kullanmayı amaçlamaktadır. Bu çalışma, betonarme yapıların sismik performansını değerlendirmek amacıyla iki temel metot olan eşdeğer deprem yükü yöntemi ve zaman tanım alanında analiz yöntemi kullanılarak binanın performansını değerlendirme ve eksik noktalarını tanımlama çalışmalarını içermektedir. Bunun yanında, binaların deprem kayıtlarına karşı performansını artırmak ve izolatörlerin kapasitelerini kontrol etmek amacıyla mevcut alçak yükseklikteki bir binada farklı tipte taban izolatör uygulamaları yoluyla bir güçlendirme stratejisi ele alınmış, ve izolatörlerin yapısal olmayan elemanların zarar görmesinin azaltılmasına yardımcı olmak ve daha yüksek katlardaki zamana bağlı hızlanmalarının nasıl azaltabildiğini kontrol etmeyi içermektedir. Yapılan analiz sonuçları, kurşun çekirdekli kauçuk izolatörünün, diğer düşünülen tiplere göre yüksek katlardaki ivmenin azaltılmasında maksimum üstün performans sergilediğini göstermiştir.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2019. Supervisor: Assoc. Prof. Dr. Mehmet Cemal Geneş.
Keywords: Civil Engineering Department; Earthquake Engineering Buildings--Earthquake effects--Seismic--Base Isolation Systems--Base Isolation Earthquake-resistant construction--Buildings Earthquake resistant design Buildings--Earthquake effects Earthquake-resistant construction--Buildings Buildings, Reinforced concrete; Reinforced concrete; base isolation; time history analysis; seismic performance; lead rubber bearing isolator; sliding isolator